Optimizing the Embankment Fill Reinforcement for Rest Area on the Semarang-Solo Toll Road with Geoframe System - Nadya Ayu Anindita; Dandung Sri Harninto; Raffly Muhammad Darmawan (Indonesian Geotechnical Journal, 2023)
On KM 456 Semarang-Solo Toll Road, a rest area which was predicted to be the grandest in Java was built. The rest area covered both sides of the toll road, which is in zone A (heading to Solo) and zone B (heading to Semarang). The rest area is built with remarkable view and unique traditional design with five roofs that represented five surrounding volcanoes. With all its philosophy, the owner sought the best option for all its structures, not only from the most economic, efficient, robust, but also the greenest option for the design. The rest area will be built on embankment with the highest being 11 meters. The embankment’s subgrade is rice field with 2 meters of soft silty clay. The initial design is to reinforce the embankment with 7-meters-tall concrete retaining wall and 2 rows of bore pile with 80 cm diameters and depth of 18 meters. This option was deemed to be very budget consuming, time consuming, and not very green. The Geoframe system, which is a combination of Geosynthetic materials, and wire mesh as facing was then chosen as the reinforcement for the embankment. The geogrid as reinforcement has proven to be very easy to install yet it’s very strong as the tensile capacity can be adjusted to the embankment’s needs. The Geoframe system can be constructed almost vertically (with a slope of 85°). Topographic data, SPT, CPT and laboratory test results were used to design a safe and efficient Geoframe system. Slope stability was analyzed using the Finite Element Method with PLAXIS 3D software. The construction carried out from 2019 to 2020 has proven that this method can be a safe, efficient, environmentally friendly option and still followed the articles stated in Indonesian National Standard for Geotechnical Design Requirements 8460: 2017.